2012
DOI: 10.1124/jpet.111.191098
|View full text |Cite
|
Sign up to set email alerts
|

The Dipeptidyl Peptidase-4 Inhibitor Linagliptin Attenuates Inflammation and Accelerates Epithelialization in Wounds of Diabetic ob/ob Mice

Abstract: In recent years, new and effective therapeutic agents for blood glucose control have been added to standard diabetes therapies: dipeptidyl peptidase-4 (DPP-4) inhibitors, which prolong the bioavailability of the endogenously secreted incretin hormone glucagon-like peptide-1 (GLP-1). Full-thickness excisional wounding was performed in wild-type (C57BL/6J) and diabetic [C57BL/6J-obese/obese (ob/ob)] mice. DPP-4 activity was inhibited by oral administration of linagliptin during healing. Wound tissue was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 45 publications
3
75
1
Order By: Relevance
“…Consistently, DPP4-I with linagliptin resulted in accelerated wound healing in diabetic obese mice compared with untreated mice. This was associated with improved reepithelialization, reduced inflammation, and enhanced the formation of myofibroblasts, all features of a healthier granulation tissue (112).…”
Section: Dpp4-i and Diabetic Foot Ulcersmentioning
confidence: 90%
See 1 more Smart Citation
“…Consistently, DPP4-I with linagliptin resulted in accelerated wound healing in diabetic obese mice compared with untreated mice. This was associated with improved reepithelialization, reduced inflammation, and enhanced the formation of myofibroblasts, all features of a healthier granulation tissue (112).…”
Section: Dpp4-i and Diabetic Foot Ulcersmentioning
confidence: 90%
“…For the possible improvement in microvascular outcomes obtained with DPP4-I as outlined above, these drugs are novel candidates for the medical treatment of diabetic foot ulcers. Experimentally, it was shown that DPP-4 expression and activity are increased in the wounded skin of diabetic obese mice (112). In turn, excess DPP-4 activity is supposed to degrade the chemokine and angiocrine factor SDF-1a (CXCL12), thus impairing vascularization and growth of the granulation tissue.…”
Section: Dpp4-i and Diabetic Foot Ulcersmentioning
confidence: 99%
“…The anti-inflammatory effects of linagliptin have been elucidated in vivo [14,[27][28][29][30]. However, to the best of our knowledge, no study has examined these effects in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…DPP IV/CD26 inhibition with linagliptin also showed decreased blood glucose levels and accelerated skin re-epithelization in diabetic mice since levels of active GLP-1 in wound lysates increased. A reduced number of neutrophils and macrophages in linagliptin-treated mice were noted [29]. DPP IV/CD26 inhibitors also show pleiotropic effects by directly changing cytokine and growth factors expression, increasing plasma levels of SDF-1α and numbers of endothelial progenitor cells in circulation, which contributes to wound healing [30].…”
Section: Dpp Iv/cd26 Inhibitors In Treatment Of Diabetesmentioning
confidence: 99%
“…Previous research has proven that DPP IV/CD26 impacts wound healing, as CD26 deficient mice showed better wound closure and scab formations compared to wild-type mice. Inhibition of DPP IV/CD26 activity during skin regeneration improves the clearance of elevated blood glucose levels and reduces high DPP IV/CD26 activity in chronic wound tissue of diabetic mice [29]. Animal studies in diabetic mice revealed increased DPP IV/CD26 levels in the presence of enhanced wound inflammatory conditions [42].…”
Section: Role Of Dpp Iv/cd26 In Wound Healing In Diabetesmentioning
confidence: 99%